Teachers’ Perceptions of Management Practices in Engineering Colleges - Chandra Mohan Singh; Sourabh Guha; Vidya Nair; Neha Soni (Scientific Research, New Technologies and Applications Vol. 3, 2024)
Teachers may be trying to update them but cost and complexity are big problems and thus this is the duty of institutions to set a system for their regular development. There is continuous change occurring in technology development and innovations in every field of life and thus engineering colleges also keep on updating teaching methodology and content so that they can continuously supply human resources with relevant employability skills. This study is conducted in private engineering colleges situated in Chhattisgarh and affiliated to CSVTU, Durg. Teachers teaching in these engineering colleges make the population and the sample is taken designation and gender-wise for the study. The teachers must match their knowledge and skills as per the requirement and the institutions should set some system to assist them in this never-ending work. Apart from direct training, another HRD practice that helps teachers in developing is knowledge management. The aim of this paper is to verify whether the knowledge management practice as a system is there in engineering institutions or not. The opinions of respondents who work as assistant professors, associate professors, and professors who instruct engineering students will be used to achieve this. A questionnaire with a five-point Likert scale will be used to gather opinions. Convenient sampling is used to obtain the samples. The group-wise opinion is derived using mean value. The hypotheses are formulated and later tested using a t-test. The overall findings suggest that the perception of teachers under study on the status of the practice of knowledge management in engineering colleges is very poor.